Analisis Determinan Motivasi Wirausaha Masyarakat Muslim Bugis di Kota Ambon - Fivit Baktirani (TAHKIM, 2013)
The aim of the study was to identify and analyze the socio-demographic, attitudinal and contextual influences on the motivation of Bugis Muslim entrepreneurs in Ambon City and to find out an Islamic economic review of the entrepreneurial motivation of the Bugis Muslim community in Ambon City. This research is a type of field research using a quantitative approach to a sample of 30 Bugis people from 30 populations in the Gedung Putih Batu Merah Ambon. Data collection was used through Likert scale measurements and analyzed through multiple linear regression analysis. The results of the study show: (1) Socio-demographic, attitudinal and contextual variables partially and simultaneously have no effect on entrepreneurial motivation. (2) In the perspective of Islamic economics, the entrepreneurship motivation of the Bugis Muslim community is relatively good where they believe that everything that success in entrepreneurship depends on sincere intentions and seeking the pleasure of Allah SWT. If someone fears Allah, he will surely be given a way out of trouble. In addition, by establishing good relationships and working sincerely, Allah will make the journey to success easier.